Architecture and Implementation of eMBMS BM-SC - Jiayu Bi; Jiangang Tong; Zheng Wang; Dandan Qin (Dianxin kexue)
On the basis of studying basic concept and standardization of BM-SC（broadcast multicast service center）, the management procedure and main service scenes of eMBMS were analyzed, then a novel architecture for eMBMS BM-SC was presented, which was under consideration of the needs of operators and in accordance with 3GPP definition. The key technologies and proposes implementation schemes of BM-SC were studied.